Análise econômica-financeira: estudo dos índices econômico-financeiros por meio das demonstrações contábeis de uma empresa do setor de transporte ferroviário - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Since 2010, Brazil has suffered a steady reduction in its Gross Domestic Product, entering into a recession in 2014. In times of crisis, the managers apply their efforts to reduce costs and increase the financial efficiency of the company. In this way, accounting is extremely important for generating information in times of crisis. The objective of this work is to present the most relevant indexes in an economic-financial analysis of a railroad company in periods of crisis, using an external user perspective. The indices used for this study are listed by Matarazzo (2010), these being the indexes of capital structure, liquidity and profitability. All the companies presented, from the year 2013, reductions or increases in their respective indices. The vertical and horizontal analyzes showed a large participation and variation of the loans and financing account, both in the short term and in the long term, and the net margin of all the companies reduced during the period. It is confirmed that each index should be analyzed in a global way, using the data from the own financial statements and external information. Isolation analyzing of the indexes does not guarantee a good understanding of the real situation of the company studied. It is also shown that each subsidiary, although operating in the same sector, has its peculiarities. The results obtained will help the managers to better define the strategies of the company, in addition to checking the strengths and weaknesses of the companies.
Keywords: Engenharia; Engenharia de produção; Análise econômico-financeira; Contabilidade; Crise; Indicadores contábeis; Economia; CNPQ::ENGENHARIAS